2004
DOI: 10.1016/s0006-3495(04)74180-6
|View full text |Cite
|
Sign up to set email alerts
|

Recording of Blue Light-Induced Energy and Volume Changes within the Wild-Type and Mutated Phot-LOV1 Domain from Chlamydomonas reinhardtii

Abstract: The time-resolved thermodynamics of the flavin mononucleotide (FMN)-binding LOV1 domain of Chlamydomonas reinhardtii phot (phototropin homolog) was studied by means of laser-induced optoacoustic spectroscopy. In the wild-type protein the early red-shifted intermediate LOV(715) exhibits a small volume contraction, DeltaV(715) = -1.50 ml/mol, with respect to the parent state. LOV(715) decays within few micro s into the covalent FMN-Cys-57 adduct LOV(390), that shows a larger contraction, DeltaV(390) = -8.8 ml/mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
72
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 53 publications
13
72
1
Order By: Relevance
“…What is clear is that LOV domains all share similar architectures and photochemical responses to illumination, harnessing the energy of incoming blue light photons to form a covalent adduct between the Sγ sulfur on a conserved cysteine residue and the C4a carbon of a flavin cofactor (12,13). Formation of this bond generates structural changes that propagate to the domain surface, altering the interactions of the core LOV domain with intra-or interprotein partners (14)(15)(16)(17)(18). For example, structural studies on Avena sativa phototropin 1 LOV2 (AsLOV2) demonstrated light-induced unfolding of the Jα-helix located C-terminal to the canonical LOV domain (15).…”
mentioning
confidence: 99%
“…What is clear is that LOV domains all share similar architectures and photochemical responses to illumination, harnessing the energy of incoming blue light photons to form a covalent adduct between the Sγ sulfur on a conserved cysteine residue and the C4a carbon of a flavin cofactor (12,13). Formation of this bond generates structural changes that propagate to the domain surface, altering the interactions of the core LOV domain with intra-or interprotein partners (14)(15)(16)(17)(18). For example, structural studies on Avena sativa phototropin 1 LOV2 (AsLOV2) demonstrated light-induced unfolding of the Jα-helix located C-terminal to the canonical LOV domain (15).…”
mentioning
confidence: 99%
“…The half-lives of the native phot and the R58K substitute were 204 and 73 s, respectively (32). To alter the lifetime of S390 in P1L2K, Arg-513 (supplemental Fig.…”
Section: Photochemistry Of P1l2k With a Substitution Of Arg-513 With mentioning
confidence: 99%
“…Both small and large amplitude conformational changes have been implicated in signal propagation by PAS domain proteins (2,21,28,(30)(31)(32); however, it has been challenging to link conformational changes to a biological function in vivo. We performed in vivo complementation studies of VVD Cys 71 Ser in Neurospora to demonstrate that light-induced conformational changes involving the N-terminal cap are essential for cellular function.…”
mentioning
confidence: 99%